Association Mapping of Selected Oil Palm Germplasm Reveals Novel and Known Genomic Regions Influencing Vegetative and Bunch Component Traits - Norhalida Mohamed Serdari; Nik Shazana Nik Mohd Sanusi; Mustafa Suzana; B S Jalani; Ian Mackay; Rajinder Singh; Maryam Mohamed Rehan; Maizura Ithnin (Springer Nature B.V., 2024)
Indexed by WOS/Scopus